WE CAME A LONG WAY IN 100 YEARS, BUT PERFECTION IS STILL A LONG WAY OFF - EISNER, JANE (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Young adults can often be recognized by their considerable skepticism, many gaps in knowledge, and even a tinge of cynicism. Accordingly, it is helpful in class when exploring utopian possibilities and dystopian hazards to highlight the record of America’s accomplishments- that is, to help college students better understand just what it is we have already accomplished, and more clearly, what it is that remains for us to tackle. A good example of this kind of reasoning and relevant data can be found in the insightful newspaper column reprinted here.